Fertilization Rapidly Alters the Feeding Activity of Grassland Soil Mesofauna Independent of Management History - Birkhofer, Klaus; Baulechner, Dennis; Diekötter, Tim; Zaitsev, Andrey; Wolters, Volkmar (Frontiers in Ecology and Evolution, 2022)
Nitrogen fertilization of permanent grasslands affects soil fauna communities by modifying their taxonomic composition, population dynamics and feeding activity. However, it is not well understood if the edaphic fauna adapts to these external inputs so that the immediate response to fertilizer application depends on the long-term nutrient management strategy. We performed a field experiment in permanent grasslands under agricultural management in three regions across Germany. We used experimental fertilization with an organic plant-sourced fertilizer along a long-term nutrient management gradient to study the immediate and long-term effects of fertilization and their interdependence on the taxonomic composition and feeding activity of the soil mesofauna (Nematoda, Oribatida, and Collembola). Sampling season, soil properties, vegetation structure, and geographic location were considered as additional predictor variables to reflect heterogeneity in environmental conditions. The taxonomic composition, richness and total abundance of soil mesofauna communities were significantly affected by long-term nutrient management, but not by experimental fertilization. However, N pulses rapidly (within days) reduced the feeding activity estimated with bait-lamina strips independent of long-term nutrient management strategies. Experimental addition of organic plant-sourced fertilizer may have led to a rapid build-up of microbial biomass, providing alternative food sources for the soil mesofauna and causing a shift away from the bait-lamina substrate. Our study indicates that community changes associated with the long-term nutrient management regime in permanent grasslands do not alter the strong functional response of the soil mesofauna to N pulses. There is an urgent need to develop nutrient management strategies for permanent grasslands that take into account both the conservation of the edaphic faunal community and changes of ecosystem functions caused by rapid responses of the soil mesofauna to fertilizer inputs.